Gambaran Regulasi Emosi Guru di Kota Padang: Gambaran Regulasi Emosi Guru Di Kota Padang - Rozi Sastra Purna (Universitas Kristen Maranatha, 2020)
Emotional regulation is the ability to recognize, monitor, and evaluate emotional responses, especially the intensity and form of reaction in achieving a goal. This study aims to investigate the teacher’s emotional regulation. This study is important to understand the mechanisms of emotion regulation, specifically among teachers. This research is descriptive in nature using quantitative approach. The sample of this study amounted to 377 Public Elementary School teachers in the city of Padang. The sampling technique used was cluster random sampling. Data were collected using emotion regulation scale. The research findings are that teacher's emotional regulation is quite high. The highest average score on the item is in the emotional monitoring aspect. While the lowest average score of items is in the aspect of modifying emotions. Primary school teachers perceive modifying emotion as something difficult to do. Whereas the aspects of monitoring and evaluating emotions tend to be in line. Teachers who are able to monitor and evaluate emotions do not modify emotions. Keywords: Teacher Regulation Emotion, Descriptive Analysis